Indigenous sex-selective salmon harvesting demonstrates pre-contact marine resource management in Burrard Inlet, British Columbia, Canada - Jesse Morin (Nature Portfolio, 2021)
Abstract To gain insight into pre-contact Coast Salish fishing practices, we used new palaeogenetic analytical techniques to assign sex identifications to salmonid bones from four archaeological sites in Burrard Inlet (Tsleil-Waut), British Columbia, Canada, dating between about 2300–1000 BP (ca. 400 BCE–CE 1200). Our results indicate that male chum salmon (Oncorhynchus keta) were preferentially targeted at two of the four sampled archaeological sites. Because a single male salmon can mate with several females, selectively harvesting male salmon can increase a fishery’s maximum sustainable harvest. We suggest such selective harvesting of visually distinctive male spawning chum salmon was a common practice, most effectively undertaken at wooden weirs spanning small salmon rivers and streams. We argue that this selective harvesting of males is indicative of an ancient and probably geographically widespread practice for ensuring sustainable salmon populations. The archaeological data presented here confirms earlier ethnographic accounts describing the selective harvest of male salmon.